2009
DOI: 10.1063/1.3266945
|View full text |Cite
|
Sign up to set email alerts
|

Streamwise oscillation of spanwise velocity at the wall of a channel for turbulent drag reduction

Abstract: Steady forcing at the wall of a channel flow is studied via direct numerical simulation to assess its ability of yielding reductions in turbulent friction drag. The wall forcing consists of a stationary distribution of spanwise velocity that alternates in the streamwise direction. The idea behind the forcing builds on the existing technique of the spanwise wall oscillation and exploits the convective nature of the flow to achieve an unsteady interaction with turbulence. The analysis takes advantage of the equiva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
139
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(164 citation statements)
references
References 30 publications
23
139
2
Order By: Relevance
“…In the oscillating-wall case, the space-averaged velocity profile follows closely the laminar solution, which has led to a scaling parameter for drag reduction (Choi et al 2002;Quadrio & Ricco 2004). Analogously, Viotti et al (2008) have found that the laminar layer induced by the standing waves agrees well with the space-averaged turbulent profile. Future work should therefore be directed at extending these results to the traveling-wave case to estimate the modification of drag.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…In the oscillating-wall case, the space-averaged velocity profile follows closely the laminar solution, which has led to a scaling parameter for drag reduction (Choi et al 2002;Quadrio & Ricco 2004). Analogously, Viotti et al (2008) have found that the laminar layer induced by the standing waves agrees well with the space-averaged turbulent profile. Future work should therefore be directed at extending these results to the traveling-wave case to estimate the modification of drag.…”
Section: Discussionsupporting
confidence: 64%
“…While purely spatial and purely temporal oscillations have been shown by Viotti et al (2008) to be largely analogous to each other, the flow response to the traveling waves is found to be interestingly complex when examined as a function of ω and κ x . Both drag reduction (DR) and drag increase (DI) may occur.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations